Bioconversion of Apple Pomace to Meyerozyma guilliermondii and Scheffersomyces stipitis Biomass - Andrea Maria Patelski; Małgorzata Ciach; Urszula Dziekońska-Kubczak; Agnieszka Nowak; Maria Balcerek; Katarzyna Pielech-Przybylska (Applied Sciences, 2024)
Poland is one of the leading apple-producing countries, both in Europe and around the world. One of the main byproducts of apple processing is pomace, which can account for 20–35% of the harvested apples. Pomace is a potential source of many valuable bioactive components and can also serve as a food ingredient, either directly or indirectly (after bioconversion with fodder yeast). This study aimed to evaluate the possibility of converting polysaccharides contained in apple pomace to yeast biomass. Meyerozyma guilliermondii and Scheffersomyces stipitis yeasts were grown in a medium prepared by pretreatment of the raw material with water or 2% sulphuric acid at 120 °C. Subsequently, enzymatic hydrolysis was performed using a Cellic CTec2 preparation at 30 °C or 50 °C. The resulting hydrolysates were enriched with ammonium salts, and shaken yeast cultures were incubated at 30 °C for 72 h. Based on the results, it can be concluded that acid pretreatment of apple pomace is more effective than water pretreatment under the same time and temperature conditions. The Meyerozyma guilliermondii strain grows in apple pomace hydrolysates more efficiently (16.29 g/L) than Scheffersomyces stipitis cells do (14.63 g/L).